2023
DOI: 10.1001/jamahealthforum.2023.1102
|View full text |Cite
|
Sign up to set email alerts
|

Association of Selected State Policies and Requirements for Buprenorphine Treatment With Per Capita Months of Treatment

Abstract: ImportanceExpanding the use of buprenorphine for treating opioid use disorder is a critical component of the US response to the opioid crisis, but few studies have examined how state policies are associated with buprenorphine dispensing.ObjectiveTo examine the association of 6 selected state policies with the rate of individuals receiving buprenorphine per 1000 county residents.Design, Setting, and ParticipantsThis cross-sectional study used 2006 to 2018 US retail pharmacy claims data for individuals dispensed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Ongoing training is critical for physicians to acquire and apply advanced skills in the care of this patient population, 305 , 306 , 307 but few opportunities exist to observe and be observed practicing new skills once required medical training is complete. The analysis of facilitators suggests skill training should focus on brief intervention (eg, screening or assessment) and on communication with patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing training is critical for physicians to acquire and apply advanced skills in the care of this patient population, 305 , 306 , 307 but few opportunities exist to observe and be observed practicing new skills once required medical training is complete. The analysis of facilitators suggests skill training should focus on brief intervention (eg, screening or assessment) and on communication with patients.…”
Section: Discussionmentioning
confidence: 99%
“…To fulfill this training requirement, much of the current workforce may complete continuing education (CE) requirements offered by academic professional societies. One recent comparative policy analysis found that state CE requirements related to addiction are associated with increased buprenorphine prescribing, 4 but further research is needed to substantiate the potential impact of CE on patient and provider outcomes. To implement effective training the Substance Abuse and Mental Health Services Administration (the federal agency responsible for creating new requirements) should create standards that allow materials to be better customized to different types of practitioners, are grounded in scientific principles of addiction treatment, and are robustly evaluated, so that non evidence-based curricula are phased out.…”
Section: Enduring Training Requirementsmentioning
confidence: 99%
“…An analysis of National Survey on Drug Use and Health (NSUDH) data, for example, found that Medicaid coverage was 14 percentage points higher pre-versus post-Expansion among impoverished people with heroin use disorder [23]. Findings on the association between Expansion and treatment for substance use disorders (SUD) are more mixed [26][27][28][29][30][31][32][33]. In an analysis of national survey data, for example, Olfson et al found no association between Expansion and the receipt of SUD treatment in the past year among people living with an SUD [28].…”
Section: Medicaid Expansion Is a Pillar Of The Patient Protection Andmentioning
confidence: 99%
“…In an analysis of national survey data, for example, Olfson et al found no association between Expansion and the receipt of SUD treatment in the past year among people living with an SUD [28]. However, studies analyzing data from SUD treatment programs, administrative claims and other sources suggest that Expansion is associated with increased SUD treatment participation among people in need [26,27,[29][30][31][32][33]. In an analysis of SUD treatment data, for example, Saloner et al found that admissions increased by one-third 4 years post-Expansion in Expansion states [27].…”
Section: Medicaid Expansion Is a Pillar Of The Patient Protection Andmentioning
confidence: 99%